An optimal operating frequency selection scheme for maximizing inductive power link efficiency. Issue 3 (5th February 2018) - Cheng, Yuhua; Xuan, Dongdong; Su, Xiang; Wu, Wei; Wang, Gaofeng
Abstract: Improving the efficiency of the inductive wireless power transfer (WPT) is an effective way to increase the power transfer distance, reduce the power exposure, and popularize the WPT application. If the geometrical sizes of the transmitting and receiving coils and the distance between them have been determined, an operating frequency exists to maximize the power transfer efficiency. In this work, a method to find this optimal frequency is introduced by virtue of analytical models of self‐ and mutual‐inductances and parasitic resistances and capacitances of the coils, and verified via simulations and measurements.